Chiral phosphoric acid-catalyzed enantioselective construction of structurally diverse benzothiazolopyrimidines. Issue 13 (27th February 2019) - Jarrige, Lucie; Glavač, Danijel; Levitre, Guillaume; Retailleau, Pascal; Bernadat, Guillaume; Neuville, Luc; Masson, Géraldine
Abstract : Chiral phosphoric acid catalyzed the formal [4+2]-cycloaddition of 2-benzothiazolimines with enecarbamates to provide benzothiazolopyrimidines with up to 99% yield and >99% ee. Abstract : A highly efficient catalytic enantioselective [4+2] cycloaddition was developed between 2-benzothiazolimines and enecarbamates. A wide range of benzothiazolopyrimidines bearing three contiguous stereogenic centers was obtained in high to excellent yields and with excellent diastereo- and enantioselectivities (d.r. > 98 : 2 and up to >99% ee). Furthermore, this chiral phosphoric acid-catalyzed strategy was scalable and enabled access to a new class of optically pure Lewis base isothiourea derivatives.